BoundaryScreen Summoning the Home Screen in VR via Walking Outward - Tian, Yang (IEEE transactions on visualization and computer graphics, 2025)
A safety boundary wall in VR is a virtual barrier that defines a safe area, allowing users to navigate and interact without safety concerns. However, existing implementations neglect to utilize the safety boundary wall's large surface for displaying interactive information. In this work, we propose the BoundaryScreen technique based on the "walking outward" metaphor to add interactivity to the safety boundary wall. Specifically, we augment the safety boundary wall by placing the home screen on it. To summon the home screen, the user only needs to walk outward until it appears. Results showed that (i) participants significantly preferred BoundaryScreen in the outermost two-step-wide ring-shaped section of a circular safety area; and (ii) participants exhibited strong "behavioral inertia" for walking, i.e., after completing a routine activity involving constant walking, participants significantly preferred to use the walking-based BoundaryScreen technique to summon the home screen